2017
DOI: 10.1007/s11356-017-9201-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxic potential of organic constituents of submicron particulate matter (PM1) in an urban road site (Barcelona)

Abstract: Atmospheric particulate matter (PM) is a recognized risk factor contributing to a number of diseases in human populations and wildlife globally. Organic matter is a major component of PM, but its contribution to overall toxicity of PM has not been thoroughly evaluated yet. In the present work, the biological activity of organic extracts from PM1 (particles with less than 1 μm of aerodynamic diameter) collected from an urban road site in the centre of Barcelona (NE Spain) was evaluated using a yeast-based assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The present study showed that SOA does not contribute to PM toxicity compared to, for example, biomass burning. Nevertheless, recent studies showed that urban SOA induced moderate effects in exposure assays [62,63,69,70]. On the other hand, risk assessment studies are in agreement with the main results of the present study, showing that ambient air pollution from biomass burning in rural-sub-urban sites represents a higher risk to develop lung cancer in humans throughout their life than pollutants that were measured in modern cities, such as Barcelona, with traffic as a dominant emission source [71].…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that SOA does not contribute to PM toxicity compared to, for example, biomass burning. Nevertheless, recent studies showed that urban SOA induced moderate effects in exposure assays [62,63,69,70]. On the other hand, risk assessment studies are in agreement with the main results of the present study, showing that ambient air pollution from biomass burning in rural-sub-urban sites represents a higher risk to develop lung cancer in humans throughout their life than pollutants that were measured in modern cities, such as Barcelona, with traffic as a dominant emission source [71].…”
Section: Discussionsupporting
confidence: 91%
“…PM immersion studies in zebrafish mimic the natural route of exposure to PM in aquatic organisms that may result from watershed runoff, ash deposits, or other forms of contamination ( Mesquita et al, 2016 , Mesquita et al, 2017 , Babić et al, 2021 ) making it a useful model for screening the ecotoxicological effects of PM and other chemicals. However, PM exposure via immersion and injection contrasts with the primary route of exposure to PM in humans, i.e., inhalation.…”
Section: Danio Reriomentioning
confidence: 99%
“…From the TEM images of the brown sample an ordered internal structure is not visible. The particles seem to consist of an oily substance (described as "condensed organic species" by Moore et al, 2014) which adheres well to the filter fibers (Fig. 10).…”
Section: Tem -Transmission Electron Microscopymentioning
confidence: 99%
“…In particular, black carbon (BC) has an important effect on radiative forcing as it has the strongest light absorption of all aerosol components (Bond and Bergstrom, 2006;IPCC, 2013). Carbonaceous material has also been found to cause various deleterious health effects (Highwood and Kinnersley, 2006;Anderson et al, 2012;Mesquita et al, 2017;EEA, 2017;Partanen et al, 2018;Rohr and McDonald, 2015).…”
Section: Introductionmentioning
confidence: 99%